Evaluation Model of Protected Fish Oil Supplementation to Realize The Quality and Productivity of Goat in The Doko District - Yulianti, Diyah Lestari; Nugroho Krisnaningsih, Aju Tjatur; Wahyu Kustyorini, Tri Ida (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The aim of this study was to evaluate the protected fish oil supplementation by calcium hydroxide in the diets for productivities of goat. The method in this study was in vivo assigned intorandomized block design with 3 treatments and three groups body weight. The treatments were R:basal diet without oil supplementation, R1: basal diet + 4% fish oil, R: basal diet + 4% Ca-fish oil. Thevariables measured [were] blood profile and body weight gain. Data analysis using Varian analysis, ifthe treatment showed significant difference, we used performed Duncan Multiple Range Test. Theresults showed that supplementation of protected fish oil by calcium hydroxide gave the realdifference (P<0.05) on decreased of total cholesterol (R2=13.67±7.02 mg/dl), decreased of LDL(R2=1.33±1.53 mg/dl), and did not significantly (P>0.05) on decreased of HDL (R2=0.33±1.15 mg/dl),and gave very real difference (P<0.01) on body weight gain (R2=50.00±2.01 g/d). It was concludedthat supplementation of protected fish oil by calcium hydroxide (R2) decreased the highest bloodprofile and increased the highest of body weight gain.Key Words: Fish Oil Protected, Calcium Hydroxide, Productivity, Quality, Goat 20